J. Edgar Thomson correspondence - Thomson, J. Edgar (John Edgar), 1808-1874.
ALS from Thomson to R. M. Magraw concerning the transport of the remains of President Zachary Taylor via railway for burial in Louisville, Ky.
Pennsylvania Railroad official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Magraw, R. M. -- Correspondence; Taylor, Zachary, -- 1784-1850 -- Death and burial; Pennsylvania Railroad; Railroads -- History; Louisville (Ky.) -- History; Railroad officials